Numerical study of atomic scale deformation mechanisms of Ti grains with different crystallographic orientation subjected to scratch testing; Applied Surface Science; Vol. 471 - Dmitriev A. I. Andrey Ivanovich; Nikonov A. Yu. Anton Yurjevich; Shugurov A. R. Artur Rubinovich; Panin A. V. Alexey Viktorovich (2019, 2019)
Title screen